Online Collaborative Learning in the Visual and Technological Education Discipline - Silva, Vítor (2017)
This paper presents a case study conducted with students of primary school analyzing the collaborative activities in a Do-It-Yourself community created on Edmodo. The study technical development is positioned in the interpretive and qualitative paradigm using the analytical content of the discussions and the created artifacts. The results show the group’s level of cooperation and the influence of some tools and working methods, making clear the need for further studies on this type of communities in these age groups, particularly on to the influence of e-moderator.